Implementation Model of Independent Learning on Arabic Learning in Higher Education - Hilmi, Danial; Toifah, Nur; Sa`diyah, Halimatus (Proceeding of International Conference on Engineering, Technology, and Social Sciences (ICONETOS), 2023)
This study aims to describe the model of implementing independent learning in Arabic language learning. This research uses a qualitative approach with multi-site research at the State Islamic Religious College in East Java which has implemented independent learning. As research objects, the Arabic Language Education study program of Maulana State Islamic University Malik Ibrahim Malang and Kediri State Islamic Institute. The data was obtained from sources, namely the head of the Arabic Language Education study program, Arabic language lecturers, and documents from implementing Arabic language learning. The data were unearthed by interview techniques, observation, and documentation studies. Data analysis techniques through Miles and Huberman techniques include data collection, condensation, data display, verification, and conclusions. Data wetness techniques with participation, the persistence of observations, triangulation, adequacy of references, checking members, detailed descriptions, and auditing. This research resulted in 1) Procedures for implementing the independent learning curriculum by preparing Standard Operating Procedures through student registration and selection, 2) Socialization of the independent learning program Arabic language education is carried out by providing information to students about the independent learning program, and 3) Conversion of the value of the independent learning program courses Arabic language education by providing elective courses that are implemented in the form of internships and adjusted with the course.